Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Here is the definition:

Bernoulli numbers arise in Taylor series in the expansion $$\frac{x}{e^x-1}=\sum_{k=0}^\infty B_k \frac{x^k}{k!}$$

I've tried to naively expand $\frac{x}{e^x-1}$ around $x_0=0$ and didn't quite understand what should be done with all the $(e^x-1)^{k+1}$ in the denominators of $f^{(k)}(0)$?

How does one get to $$1 - \frac{x}{2} + \frac{x^2}{12} - \frac{x^4}{720} + \ ...$$ directly from the definition (without rearranging the whole thing into the recursive formula)?

Thanks a lot!

share|cite|improve this question
This is the exponential generating function of Bernoulli numbers – Mhenni Benghorbal May 4 '13 at 12:39
up vote 4 down vote accepted

Expand $e^{x}$ around $x=0$ and then reexpand \begin{align}\frac{1}{1+\frac{x}{2!}+\frac{x^2}{3!}+\ldots}=1-\left(\frac{x}{2!}+\frac{x^2}{3!}+\frac{x^3}{4!}\ldots\right)+\left(\frac{x}{2!}+\frac{x^2}{3!}+\ldots\right)^2-\left(\frac{x}{2!}+\ldots\right)^3+\ldots=\\ =1-\left(\frac{x}{2}+\frac{x^2}{6}+\frac{x^3}{24}+\ldots\right)+\frac{x^2}{4}\left(1+\frac{x}{3}+\ldots\right)^2-\frac{x^3}{8}\left(1+\ldots\right)^3+\ldots=\\ =1-\left(\frac{x}{2}+\frac{x^2}{6}+\frac{x^3}{24}\right)+\frac{x^2}{4}\left(1+\frac{2x}{3}\right)-\frac{x^3}{8}+O\left(x^4\right)=\\ =1-\frac{x}{2}+\left(-\frac{1}{6}+\frac14\right)x^2+\left(-\frac{1}{24}+\frac{1}{6}-\frac{1}{8}\right)x^3+O\left(x^4\right)=\\ =1-\frac{x}{2}+\frac{x^2}{12}+O\left(x^4\right).\end{align}

share|cite|improve this answer
Could you please elaborate how to get from your RHS to $1 - \frac{x}{2} + \frac{x^2}{12} - \frac{x^4}{720} + \ ...$? – Leo May 4 '13 at 12:42

I know that the question asks for a method not using recursion, but this is just so much easier and cleaner than computing the series for $\dfrac{x}{e^x-1}$.

Given $$ \frac{x}{e^x-1}=\sum_{k=0}^\infty B_k\frac{x^k}{k!}\tag{1} $$ we can rewrite $(1)$ as $$ \begin{align} 1 &=\sum_{j=0}^\infty\frac{x^j}{(j+1)!}\sum_{k=0}^\infty B_k\frac{x^k}{k!}\\ &=\sum_{k=0}^\infty x^k\sum_{j=0}^k\frac{B_{k-j}}{(k-j)!\,(j+1)!}\\ &=\sum_{k=0}^\infty\frac{x^k}{(k+1)!}\sum_{j=0}^k\binom{k+1}{j+1}B_{k-j}\tag{2} \end{align} $$ which yields $B_0=1$ and the recurrence $$ B_k=-\frac1{k+1}\sum_{j=1}^k\binom{k+1}{j+1}B_{k-j}\tag{3} $$ for $k\ge1$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.